The Relationship Between Computer Vision Syndrome and Sleep Quality of Undergraduate Nursing Students - Tampubolon, Lindawati Farida; Tumanggor, Lili Suryani; Harefa, Salvia Elvaretta (Poltekkes Kemenkes Surakarta, 2025)
Background: Complex vision problems experienced when using digital devices are called Computer Vision Syndrome (CVS). The use of digital devices at night affects the delay of the circadian phase and the suppression of melatonin as a sleep facilitator which causes changes in sleep quality and optimizes cognitive abilities. This study aims to determine the relationship between computer vision syndrome and student sleep quality. Methods: This research uses a correlational design with a cross-sectional approach. Sampling used proportionate stratified random sampling technique with a total of 198 respondents. The incidence of CVS was measured by the Computer Vision Syndrome-Questionnaire (CVS-Q) and sleep quality by the PSQI (Pitssburgh Sleep Quality Index) questionnaire. Bivariate analysis was conducted with CVS as the independent variable and sleep quality as the dependent variable, using the continuity correction test. Results: The research results show that 80.8% of respondents experienced CVS-Positive and 80.8% of respondents experienced poor sleep quality. The statistical test results obtained p-value = <0.001 (< α 0.05) with an OR value of 71.25. Conclusion: Thus, it can be concluded that computer vision syndrome is related to student sleep quality, where positive computer vision syndrome has the potential to cause disruption to student sleep quality 71.25 compared to students who have negative CVS. Nursing students are advised to limit excessive use of digital devices and to adopt healthy habits in screen usage to prevent CVS, which can affect sleep quality.